2012
DOI: 10.1021/ja211380p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Activation and Metal Hydride Formation Trigger Cluster Formation from Supported Iridium Complexes

Abstract: The formation of iridium clusters from supported mononuclear iridium complexes in H(2) at 300 K and 1 bar was investigated by spectroscopy and atomic-resolution scanning transmission electron microscopy. The first steps of cluster formation from zeolite-supported Ir(C(2)H(4))(2) complexes are triggered by the activation of H(2) and the formation of iridium hydride, accompanied by the breaking of iridium-support bonds. This reactivity can be controlled by the choice of ligands on the iridium, which include the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 36 publications
5
74
0
1
Order By: Relevance
“…We recognize that, in previous work,25 samples similar to ours incorporating iridium complexes bonded to HY zeolite were characterized by an IR band at 2068 cm −1 (which we have attributed to a carbonyl band), and the authors suggested that it was evidence of an IrH vibration because they inferred that it “shifted” to 1509 cm −1 after an isotopic exchange with D 2 . However, the apparent shift does not match the frequencies calculated in the harmonic approximation,21 and we suggest that it was indeed a carbonyl band (which might have arisen from trace CO impurities).…”
Section: Resultsmentioning
confidence: 49%
“…We recognize that, in previous work,25 samples similar to ours incorporating iridium complexes bonded to HY zeolite were characterized by an IR band at 2068 cm −1 (which we have attributed to a carbonyl band), and the authors suggested that it was evidence of an IrH vibration because they inferred that it “shifted” to 1509 cm −1 after an isotopic exchange with D 2 . However, the apparent shift does not match the frequencies calculated in the harmonic approximation,21 and we suggest that it was indeed a carbonyl band (which might have arisen from trace CO impurities).…”
Section: Resultsmentioning
confidence: 49%
“…[4c] In contrast, the higher stability of the analogous iridium complexes demonstrated by our results (both experimental and computational) allows a resolution of the reaction network accounting for the corresponding conversions involving the iridium complexes, as shown in Scheme 1. [7,11] Thus, in Scheme 1 we propose the formation of Ir(C 2 H 5 )(H) as an intermediate after exposure of the sample to H 2 and before the adsorption of a dinitrogen ligand. [10] When the sample came in contact with H 2 at room temperature, an ethylene ligand on iridium was rapidly transformed to C 2 H 5 , with a hydride ligand presumably formed on the Ir atom, and with C 2 H 4 being displaced.…”
Section: Discussionmentioning
confidence: 99%
“…[10] When the sample came in contact with H 2 at room temperature, an ethylene ligand on iridium was rapidly transformed to C 2 H 5 , with a hydride ligand presumably formed on the Ir atom, and with C 2 H 4 being displaced. [7,11] Thus, in Scheme 1 we propose the formation of Ir(C 2 H 5 )(H) as an intermediate after exposure of the sample to H 2 and before the adsorption of a dinitrogen ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The process typically involves reduction, migration of metal species on the support surface, and metal-metal bond formation processes, as demonstrated particularly by Gates and coworkers (154).…”
Section: (B) Models Involving Transition Metals Other Than Ironmentioning
confidence: 99%
“…In this regard, the hydrogen spillover concept employed by Gates and coworkers to explain their results (154), is terra incognita for DHC purposes still full of controversies, especially for the transfer of hydrogen species onto the non reducible support surfaces (155). Our ongoing work on spillover of hydrogen based on combined Pd/SiO 2 clusters (Pd 4 tetrahedral cluster located on top of the cyclic silica consisting of three SiO 4 -linkages) indicates the main role of the H 2 -catalyst (the transporter of the spillover-hydrogen species), and the adsorbed (capped on palladium vertexes) hydrogen molecules (151).…”
Section: (B) Models Involving Transition Metals Other Than Ironmentioning
confidence: 99%